Regional economic development: Rethinking the region - Nik Muhammad, Nik Maheran; Md Isa, Filzah; Othman, Siti Norezam; Che Yaacob, Haslina (Global Strategic Management Incorporated, USA, 2011)
The main objective of this article is to determine the factors that contribute to the construction and destruction of regional economic development. Various theories were formulated for the conclusion of this article.Among the theory reviewed was Schumpeterian model (1950) of social inequalities, Borts and Stein (1964) theory of employment change, human capital and social capital theory.A comprehensive conceptual framework of Regional Economic Development was proposed by determining the factors that contribute to regional economic development performance. In attaining regional development, the leadership of the state is proposed to inculcate the Islamic values in administrating and making decision for the development of the region.